Mitigating Scar Tissue Formation in Tendon Injuries: Targeting HMGB1, AMPK Activation, and Myofibroblast Migration All at Once - Jianying Zhang; Roshawn Brown; MaCalus V. Hogan; James H-C. Wang (MDPI AG, 2023)
Tendon injuries, while prevalent, present significant challenges regarding their structural and functional restoration. Utilizing alpha-smooth muscle actin (α-SMA)-Ai9-scleraxis (Scx)-green fluorescent protein (GFP) transgenic mice, which exhibit both Scx (a tendon cell marker) and α-SMA (a myofibroblast marker), we explored the effects of metformin (Met) on tendon healing, repair, and its mechanisms of action. Our findings revealed that intraperitoneal (IP) injections of Met, administered before or after injury, as well as both, effectively prevented the release of HMGB1 into the tendon matrix and reduced circulating levels of HMGB1. Additionally, Met treatment increased and activated AMPK and suppressed TGF-β1 levels within the healing tendon. Tendon healing was also improved by blocking the migration of α-SMA+ myofibroblasts, reducing the prevalence of disorganized collagen fibers and collagen type III. It also enhanced the presence of collagen type I. These outcomes highlight Met's anti-fibrotic properties in acutely injured tendons and suggest its potential for repurposing as a therapeutic agent to minimize scar tissue formation in tendon injuries, which could have profound implications in clinical practice.